The Extraterrestrial Dust Flux: Size Distribution and Mass Contribution Estimates Inferred From the Transantarctic Mountains (TAM) Micrometeorite Collection. Issue 2 (13th February 2020) - Suttle, M. D.; Folco, L.
Abstract: This study explores the long‐duration (0.8–2.3 Ma), time‐averaged micrometeorite flux (mass and size distribution) reaching Earth, as recorded by the Transantarctic Mountains (TAM) micrometeorite collection. We investigate a single sediment trap (TAM65), performing an exhaustive recovery and characterization effort and identifying 1, 643 micrometeorites (between 100 and 2, 000 μm). Approximately 7% of particles are unmelted or scoriaceous, of which 75% are fine‐grained. Among cosmic spherules, 95.6% are silicate‐dominated S‐types, and further subdivided into porphyritic (16.9%), barred olivine (19.9%), cryptocrystalline (51.6%), and vitreous (7.5%). Our (rank)‐size distribution is fit against a power law with a slope of −3.9 ( R 2 = 0.98) over the size range 200–700 μm. However, the distribution is also bimodal, with peaks centered at ~145 and ~250 μm. Remarkably similar peak positions are observed in the Larkman Nunatak data. These observations suggest that the micrometeorite flux is composed of multiple dust sources with distinct size distributions. In terms of mass, the TAM65 trap contains 1.77 g of extraterrestrial dust in 15 kg of sediment (<5 mm). Upscaling to a global annual estimate gives 1, 555 (±753) t/year—consistent with previous micrometeorite abundance estimates and almost identical to the South Pole Water Well estimate (~1, 600 t/year), potentially indicating minimal variation in the background cosmic dust flux over the Quaternary. The greatest uncertainty in our mass flux calculation is the accumulation window. A minimum age (0.8 Ma) is robustly inferred from the presence of Australasian microtektites, while the upper age (~2.3 Ma) is loosely constrained based on 10 Be exposure dating of glacial surfaces at Roberts Butte (6 km from our sample site). Plain Language Summary: Each year the Earth collects large amounts of extraterrestrial material, with a significant fraction in the form of submillimeter cosmic dust, originating from asteroids and comets. This material adds elements such as nickel and sodium to the Earth's atmosphere, which effect the ionosphere. In the past, cosmic dust may have also played an important role in the origin of life as well as potentially contributing to mass extinction events. Here we examine an ancient (>0.8‐million‐year‐old) micrometeorite collection found among the Transantarctic Mountains. We estimate the quantity of cosmic dust falling to Earth over this time period to be between (approximately) 800 and 2, 300 tons per year. In addition, we demonstrate that the cosmic dust flux contains at least two dominant sources with different size distributions. This could reflect the relative contributions from inner solar system asteroids and outer solar system comets. Key Points: Antarctic micrometeorite collections are time‐averaged windows of the cosmic dust flux, in terms of mass, size and composition The near‐Earth cosmic dust complex has a bimodal size distribution, as inferred from micrometeorite collections at the Earth's surface The average flux of cosmic dust to Earth over the Quaternary, inferred from the TAM65 trap lies between ~800 and 2, 300 t/yr